Polyethersulfone Mats Functionalized with Porphyrin for Removal of Para-nitroaniline from Aqueous Solution - Gangemi, Chiara Maria Antonietta (Molecules, 2019)
The dispersion of para-nitroaniline (p-NA) in water poses a threat to the environment and human health. Therefore, the development of functional adsorbents to remove this harmful compound is crucial to the implementation of wastewater purification strategies, and electrospun mats represent a versatile and cost-effective class of materials that are useful for this application. In the present study, we tested the ability of some polyethersulfone (PES) nanofibers containing adsorbed porphyrin molecules to remove p-NA from water. The functional mats in this study were obtained by two different approaches based on fiber impregnation or doping. In particular, meso-tetraphenyl porphyrin (H(2)TPP) or zinc(II) meso-tetraphenyl porphyrin (ZnTPP) were immobilized on the surface of PES fiber mats by dip-coating or added to the PES electrospun solution to obtain porphyrin-doped PES mats. The presence of porphyrins on the fiber surfaces was confirmed by UV–Vis spectroscopy, fluorescence measurements, and XPS analysis. p-NA removal from water solutions was spectrophotometrically detected and evaluated.